2013
DOI: 10.3109/02713683.2013.809768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silicone Hydrogel Contact Lenses on Ocular Surface After Sub-Bowman’s Keratomileusis

Abstract: Silicone hydrogel contact lenses played a positive role in accelerating corneal epithelial healing, enhancing tear film stability and reducing discomfort of patients in the early stage after SBK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The use of BCLs in refractive surgeries such as PRK and LASEK has been proven to be effective and safe [ 4 , 5 ]. Studies have also shown that BCLs applied immediately after LASIK can reduce flap complications and patient discomfort after surgery [ 6 , 17 ]. As SMILE is a relatively new type of refractive surgery, the clinical use of BCLs for the improvement of patients' comfort is not fully understood and requires further assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of BCLs in refractive surgeries such as PRK and LASEK has been proven to be effective and safe [ 4 , 5 ]. Studies have also shown that BCLs applied immediately after LASIK can reduce flap complications and patient discomfort after surgery [ 6 , 17 ]. As SMILE is a relatively new type of refractive surgery, the clinical use of BCLs for the improvement of patients' comfort is not fully understood and requires further assessment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in LASIK patients, the speed of corneal epithelium healing was faster in SiH CL wearers (4.1 ± 0.3 days) when compared to hydrogel lens wearers (4.3 ± 0.8 days) [ 13 ]; whilst another study showed that eighty percent of eyes with a SiH CLs versus 63% of eyes with hydrogels had grade 1 epithelial recovery at 5 days postsurgery [ 12 ]. Gao et al [ 17 ] also found that the corneal thickness of eyes in silicone hydrogel lens were thinner than those wearing hydrogel lens at 1 day after Sub-Bowman keratomileusis (SBK) surgery. More investigations are needed to confirm if SiH BCLs may further assist, as the results of this study suggested, in preventing or alleviating corneal oedema related with surgery procedures after SMILE.…”
Section: Discussionmentioning
confidence: 99%
“…Before surgery and 1 day, 1 week, 1 month, 3 months postoperatively, the following ocular surface parameters were evaluated on all participants as previously described [25]: corneal fluorescein (FL) staining, tear break-up time (TBUT), Schirmer I test (SIT), ocular surface disease index (OSDI) and central corneal sensitivity. OSDI, a 12-question survey, is one of the most widely used tools for dry eye patients to report their symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Chapter 2: Evaluating questionnaires assessing contact lens dissatisfaction from contact lens discomfort and binocular vision disorders as a factor for DED, 81,[421][422][423][424][425][426][427][428][429][430][431][432][433] dry eye interventions involving CL use, 177,[434][435][436][437] therapeutic interventions while wearing CLs, 438 and to categorise CL wearers as those with or without CLD. 15 OSDI has also been shown to correlate with both CLDEQ-8 and CISS.…”
Section: Thesis Overviewmentioning
confidence: 99%